2021
DOI: 10.1111/cyt.12994
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ROS1 by immunohistochemistry against fluorescent in situ hybridisation on cytology and small biopsy samples in a large teaching hospital

Abstract: Objective Rearranged ROS1, present in 1%‐2% of non‐small cell lung cancer (NSCLC) patients, usually young, never or light smokers, is assessed by fluorescence in situ hybridization (FISH) to determine eligibility for tyrosine kinase inhibitors (TKI). Immunohistochemistry (IHC) for the protein product of ROS1 rearrangement, a cost‐effective alternative, is validated on cytology and small biopsy samples. Methods From 1 March to 31 December 2019, cytology cell blocks and small biopsy samples from a selected cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Immunohistochemistry was requested once the H&E was examined, and tumour content assessed. Small (5 × 5 μm) sections were cut and sent to the molecular diagnostics department for EGFR analysis and additional sections were cut for ALK, ROS‐1 and PD‐L1 analysis by IHC in that order 10 . Turnaround time (TAT) for IHC is usually 24 hours from time of request whilst that of EGFR was 7–10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was requested once the H&E was examined, and tumour content assessed. Small (5 × 5 μm) sections were cut and sent to the molecular diagnostics department for EGFR analysis and additional sections were cut for ALK, ROS‐1 and PD‐L1 analysis by IHC in that order 10 . Turnaround time (TAT) for IHC is usually 24 hours from time of request whilst that of EGFR was 7–10 days.…”
Section: Methodsmentioning
confidence: 99%
“…Crizotinib and entrectinib are currently approved for first‐line therapy of ROS1 ‐positive NSCLC, with the latter generally preferred in case of brain involvement at initial diagnosis 39,42–44 . ROS1 fusions can be assessed on a tissue biopsy and cytological samples using ROS1 IHC, but similar to the ALK IHC, ROS1 IHC can have false positives and therefore needs confirmation by ROS1 FISH, NGS, or with a multiplex RT‐PCR panel 22,45–48 . ROS1 rearrangement can be assessed using plasma samples and some multiplex RT‐PCR method or NGS 49 .…”
Section: Alk Ros1 Ntrk and Ret Fusions: The “Big Four” Fusion Targets...mentioning
confidence: 99%
“…39,[42][43][44] ROS1 fusions can be assessed on a tissue biopsy and cytological samples using ROS1 IHC, but similar to the ALK IHC, ROS1 IHC can have false positives and therefore needs confirmation by ROS1 FISH, NGS, or with a multiplex RT-PCR panel. 22,[45][46][47][48] ROS1 rearrangement can be assessed using plasma samples and some multiplex RT-PCR method or NGS. 49 Finally, a few studies showed the possibility of detecting a ROS1 fusion in circulating tumor cells (CTCs), but no routine clinical practice has yet been established.…”
Section: Ros1 Rearrangementsmentioning
confidence: 99%
“…Recently, Narine et al have published their methodology for validating ROS1 immunohistochemistry on CBs against fluorescence in situ hybridisation (FISH). 86 Control material should be prepared by the same method as the test sample, 87 which can pose problems given the rarity of positive cases with ROS1 and ALK. As tissue sections are the most frequently used control material, 84 formalin-fixed CBs prepared from samples not pre-fixed in alcohol are the most practical.…”
Section: B Iomarker Immunoc Y Tochemis Trymentioning
confidence: 99%
“…As with diagnostic ICC markers, rigorous local validation is essential, particularly given the therapeutic implications of biomarker positivity. Recently, Narine et al have published their methodology for validating ROS1 immunohistochemistry on CBs against fluorescence in situ hybridisation (FISH) 86 …”
Section: Biomarker Immunocytochemistrymentioning
confidence: 99%